Massive hemorrhage management-a best evidence topic report - Vymazal, Tomas (Therapeutics and clinical risk management, 2015)
INTRODUCTION: Massive hemorrhage remains a major cause of potentially preventable deaths. Better control of bleeding could improve survival rates by 10%-20%. Transfusion intervention concepts have been formulated in order to minimize acute traumatic coagulopathy. These interventions still have not been standardized and vary among medical centers. MATERIALS AND METHODS: Based on a literature search using free term keywords and Medical Subject Heading (MeSH) index, we analyzed published articles addressing massive hemorrhage, component therapy, fresh whole blood, and fibrinogen from the year 2000 onward, in journals with impact factor >1.000, in Medline, PubMed, and Google Scholar. The evidence was grouped into topics including laboratory testing and transfusion interventions/viscoelastic assays vs standard laboratory tests, the effect of component therapy on patient outcome, the effect of warm fresh whole blood on patient outcome, and the effects of fibrinogen in severe bleeding. The obtained information was compared, evaluated, confronted, and was focused on to present an adequate and individual-based massive hemorrhage management approach. RESULTS: Viscoelastic whole-blood assays are superior to standard coagulation blood tests for the identification of coagulopathy and for guiding decisions on appropriate therapy in patients with severe bleeding. Replacement of plasma, red blood cells, platelets, and fibrinogen in a ratio of 1:1:1:1 has appeared to be the best substitution for lost whole blood. There is no evidence that cryoprecipitate improves the outcome of patients with severe hemorrhage. Current literature promotes the transfusion of warm fresh whole blood, which seems to be superior to the component therapy in certain clinical situations. Some authors recommend that fibrinogen and other coagulation factors be administered according to the viscoelastic attributes of the blood clot. CONCLUSION: This best-evidence topic report brings comprehensive information about massive hemorrhage management.
Keywords: transfusion; fibrinogen; coagulopathy; viscoelastic assay